PEMBERDAYAAN MASYARAKAT DI DESA GADING WETAN MELALUI RUKUN KEMATIAN - Rahmah, Chovivatur; Sya’baniya, Diyah Ayu; Rahmah, Faizatur; Hernika, Hernika; Hasanah, Maulidatul; El-Hamziyah, Millatul Fitriyah; Silviana, Nadzirah; Yanti, Yanti (Kalam Nusantara Institute, 2024)
Gading Wetan Village is a village that has many assets. These assets include manaqib every 11 hijriyah, rukun death, nightly routines (Saturday, Tuesday and Thursday) khotmil quran (Wednesday and sarwa). One of the activities that we think is very unique is the Rukun Death, because not many villages hold this activity. The method used is the ABCD method. From there our group was interested in developing the Harmony of Death activities in Gading Wetan Village. Seeing that many people did not understand how to take care of corpses, our group took the initiative to hold training activities for taking care of corpses. The evaluation results from this Community Service activity show that the people of Gading Wetan really benefit from all the material that has been provided to increase their knowledge in caring for corpses so that the community no longer has differences of opinion.